Implementation of The Pancasila Student (P5) Profile Strengthening Project in Forming Students' Entrepreneurial Character at Poboya State Primary School - Masliati; Santi, Ira Nuriya; Zahara, Zakiyah; Palawa, Muh. Riswandi (PT. Global World Scientific, 2024)
The Project to Strengthen the Pancasila Profile (P5) is an educational initiative that aims to introduce the concept of entrepreneurship to students. This article aims to fill the knowledge gap and contribute to understanding how P5 can effectively shape the entrepreneurial character of students in primary schools. The type of research used in this research is qualitative research methods. The research location that the researcher used as the object of this research was SD Negeri Poboya, located at Jl. Pue Salanga No. 36, Poboya District. Mantikulore, Palu city, Central Sulawesi. Data collection techniques in this research were through observation and interviews. The data source for this research is the driving teacher at Poboya State Elementary School. The research results show that P5 has a significant influence on forming the entrepreneurial spirit of students. The role of P5 in education is very supportive in forming students' entrepreneurial character. With a long duration of 7 hours a day, students can express their entrepreneurial abilities.